Microbial metabolic activity in Amazon floodplain forest and agricultural soils - Barros, Dayane J.; Carvalho, Glauber A.; de Chaves, Miriam G.; Vanzela, Luiz S.; Kozusny-Andreani, Dora Inés; Guarda, Emerson A.; Neu, Vania; de Morais, Paula B.; Tsai, Siu M.; Navarrete, Acacio A. (Frontiers in Microbiology, 2023)
Microorganisms play an essential role in ecosystem functions. An increasingly used method for conducting functional analyses of a soil microbial community is based on the physiological profile at the community level. This method allows the metabolic capacity of microorganisms to be assessed based on patterns of carbon consumption and derived indices. In the present study, the functional diversity of microbial communities was assessed in soils from seasonally flooded-forest (FOR) and -traditional farming systems (TFS) in Amazonian floodplains flooded with black, clear, and white water. The soils of the Amazon floodplains showed differences in the metabolic activity of their microbial communities, with a general trend in activity level of clear water floodplain > black water floodplain > white water floodplain. The redundancy analysis (RDA) indicated that soil moisture (flood pulse) was the most important environmental parameter in determining the metabolic activity of the soil microbial communities in the black, clear, and white floodplains. In addition, the variance partitioning analysis (VPA) indicated that the microbial metabolic activity of the soil was more influenced by water type (41.72%) than by seasonality (19.55%) and land use type (15.28%). The soil microbiota of the white water floodplain was different from that of the clear water and black water floodplains in terms of metabolic richness, as the white water floodplain was mainly influenced by the low substrate use during the non-flooded period. Taken together, the results show the importance of considering soils under the influence of flood pulses, water types, and land use as environmental factors when recognizing functional diversity and ecosystem functioning in Amazonian floodplains.